Um estudo sobre a cultura lúdica de crianças sem recreio - Carvalho, Eva Laura Silva Fortes de (2021)
The research in question is an investigation into the play culture of children in basic education with the absence of recess. The break, as this school rite is called, must be understood as the time of possible interaction with the other and the manifestation of different cultural forms of movement. For such an endeavor we make use of the studies and research of Gilles Brougère (1998); Brian Sutton-Smith (2017); Jean Château (1987); Roger Caillois (1990), among other authors who help us answer the questions: 1) What learning: intellectual, motor, affective, symbolic and moral learning are expressed in the play of children without recess? 2) Can the lack of recess lead children to "risky behavior2 " in the exercise of play culture? 3) Do the school management team and teachers have knowledge about playful-recreational activities for this age group (6 to 7 years old)? 4) What are the children's favorite games that allow them to live their ludic culture in the playground or non-playground spaces. An ethnographic research, guided by the study of essences, which takes place in existence and in life, whose greatest effort was to describe, much more than explain or analyze, but, to subsidize the methodological support presented to the investigation as suggested by Bogdan and Biklen (1994); Manoel Sarmento (2003); Lüdke and André (2018). The locus of the research was a Basic Education unit, located in the municipality of Cuiabá-MT. The research participants were students of the 1st year of elementary school, teachers and members of the pedagogical body who were willing to participate in the research. It should be noted that this research was conducted during the Covid-19 pandemic, with Research Ethics Committee approval number 4,658,768. It was found that the work done collected, from theoretical studies, data that composed this dissertation to what constitutes the culture of play, the importance of social interaction in the school environment and the experience of recreation, showing how important play is to the formation of these children, even if there is no time and space for recreation. In playing, necessarily, meanings and processes are apprehended. Therefore, the playful forms of social interaction are access routes to culture; they are the bridges that connect children with the most elementary aspects of school organization and their environment.